Hepatitis B Vaccination Coverage and Its Associated Factors in Nurses of Imam Reza (AS) Hospital in Kermanshah - Edris Abdifard; Azadeh Faraji; Elham Sepahvand; Abbas Aghae; Alice Khachian (Iran University of Medical Sciences, 2016)
Background: Viral hepatitis is one the main infections that health staff are faced with and nurses are at greater risk of the contracting this disease because of their exposure to patients. The current study was conducted to determine the hepatitis B vaccination coverage and its associated factors in nurses of Imam Reza (AS) Hospital in Kermanshah, Iran. Methods: In this descriptive-analytic study, 258 nurses working in Imam Reza (AS) Hospital of Kermanshah were studied based on census records in 2012. Instrument for the data collection was a researcher-made questionnaire, which its validity and reliability were approved. Collected data were analyzed by the Chi-square and ANOVA tests using SPSS 16. Results: Out of 258 nursing staff, 85.2% had completed vaccination, 3.9% had it once, and 10.9% had received two shots of vaccine. Among the most important barriers to vaccination mentioned by the participants were forgetting (57.2%), negligence (39.5%), and high workload (36.8%). Conclusion: Given the relatively high coverage of vaccination in this study, to maintain the efficiency of nurses as well as reducing the cost of difficult treatment of hepatitis B, necessary facilities and education about the disease and its complications should be provided by the authorities for the full vaccination coverage at very low cost.